Cryogenic preservation of embryos of Prochilodus lineatus (Valenciennes, 1836) (Characiforme; Prochilodontidae) - Ninhaus-Silveira, Alexandre; Foresti, Fausto [UNESP]; de Azevedo, Alexandre; Agostinho, Claudio Angelo [UNESP]; Verissimo-Silveira, Rosicleire (Cambridge University Press, 2009)
While the freezing techniques of mammal embryos have been providing promising results, the cryopreservation of teleostean eggs and embryos have remained unsuccessful up to now. Therefore, this work aimed to develop a procedure of cryogenic preservation of embryos of Prochilodus lineatus and to observe, at both structural and ultrastructural levels, the morphological alterations that took place after the application of freezing/thawing techniques. The embryos at the morula stage could not tolerate exposure to the cryoprotectants ethylene glycol monomethyl ether, propylene glycol monomethyl ether, methanol, dimethyl sulphoxide and propylene glycol, presenting 100% of mortality. Embryos at the 4- to 6-somites stage tolerated exposure to propylene glycol and dimethyl sulphoxide, and the results revealed no significant differences (alpha = 0.05) regarding survival from both treatments. None of the freezing, thawing and hydration protocols was effective on preserving embryo viability. The ultrastructural analyses of frozen and thawed embryos showed that cells from ectoderm, somites, notochord and endoderm were structurally intact, with well preserved nuclei and mitochondria. The yolk globules were able to tolerate the freezing process, but the yolk syncytial layer was unorganized, displaying an electron-dense and compacted appearance, collapsed reticules, nuclei with modified chromatin and ruptures on the plasmatic membrane at the contact zone with endoderm. It might be concluded that the procedures tested for freezing were unable to avoid the formation of intracellular ice crystals, leading to drastic morphological modifications and making P. lineatus embryos unviable.
Keywords: Cryopreservation; Embryo; Prochilodus lineatus; Toxicity